2004
DOI: 10.2176/nmc.44.118
|View full text |Cite
|
Sign up to set email alerts
|

Combined Approach for Far-Lateral Lumbar Disc Herniation

Abstract: This study evaluated the combination of the classical interlaminar approach and the intertransverse route through a midline approach for the treatment of 18 patients with far-lateral lumbar disc herniations, as identified by magnetic resonance imaging. The patients presented with acute severe sciatica, antalgic posture, positive Las àegue sign and femoral stretch test, motor and sensory deficits, and reflex loss findings. Discectomy of all 18 patients was performed by the combined approach. Neurological outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…Porchet, evaluating the largest series of patients after 4.2 years, found excellent and good outcomes in 73% of his 202 patients [19]. More favorable are the reports of Weiner [27] and Ozveren [18] with excellent and good results in 85 and 100%, respectively, of their patients after 5-8 years. Epstein, comparing different surgical procedures, found excellent and good results after 5 years ranging from 68 to 79%.…”
Section: Clinical Resultsmentioning
confidence: 94%
“…Porchet, evaluating the largest series of patients after 4.2 years, found excellent and good outcomes in 73% of his 202 patients [19]. More favorable are the reports of Weiner [27] and Ozveren [18] with excellent and good results in 85 and 100%, respectively, of their patients after 5-8 years. Epstein, comparing different surgical procedures, found excellent and good results after 5 years ranging from 68 to 79%.…”
Section: Clinical Resultsmentioning
confidence: 94%
“…[2][3][4][5][6][7] The use of axial CT scans and MRI facilitate the diagnosis of far lateral disc herniations, [8][9][10] which comprise 2.6-11.7% of all lumbosacral disc herniations. [11][12][13][14] The relatively high rate of far lateral disc herniations, and reports of unsuccessful results with classical surgical approaches to them have led to the use of extraforaminal approaches since the 1980 s. 15 A variety of far lateral approaches have been described for far lateral disc herniations below the L2-L3 intervertebral disc space. 11 Each has advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][16][17][18][19][20][21][22][23] FLLDHs constitute B4% to 7% of all lumbar disc herniations. [1][2][3][4][5][6][7][8][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][22][23][24] In 1974, Abdullah et al 1 were the first to describe the clinical syndrome of far-lateral lumbar disc herniation (FLLDHs). The first extraforaminal microsurgical approach was used by Reulen et al …”
Section: Discussionmentioning
confidence: 99%
“…FLLDHs were first described by Abdullah and coworkers 1 in 1974 and the clinical features have often been discussed since then. [2][3][4][5][6][7][8][12][13][14][15][16][17][18][19][20][22][23][24][25][26][27] Use of posterior lateral approaches, either para-muscular or intramuscular, both sparing the articular facets, has thus emerged as a better option. The posterior lateral approach was initially developed for lumbar arthrodesis, as described by Wiltse et al 29 Nevertheless, only in 1985, RecoulesArche 30 reported his experience with the transmuscular approach for the surgical treatment of foraminal and extraforaminal disc herniations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation